Investigation of the National Newborn Hearing Screening Program Based on Family and Health Workers' Opinions: A Case Study - Nagihan Baş; Zerrin Turan; Yıldız Uzuner (Anı Publishing, 2019)
This qualitative study aims to investigate the process in the newborn hearing screening program of a referral hospital. The health workers and parents of children who were diagnosed with a hearing loss were interviewed to gather the data. The participants of the study were four audiometrist, an audiologist, an ear nose throat surgeon and seven families. The data were collected through semi-structured interviews with participants, observations of reference hospital, documents, artifacts and the researcher's journal. The data were analyzed and interpreted inductively. The results of the study indicated that the quantity of the reference and early intervention centers need to be increased by the state. The families were expressed their need for economic and psychological support. An efficient feedback system was suggested to decrease the loss to follow up by the health workers. The need for improved co-operation between the health workers and educators was also stressed.